An analysis of the quality of information used for decision making by CPPTAE/UFRN - Cavalcante, Adam Rafael Gonçalves; Martins, Daniel de Araújo (Ciência da Informação em Revista, 2024)
Faced with the constant need to improve its management of technical-administrative personnel, the Federal University of Rio Grande do Norte created its own Commission for Technical-Administrative Personnel in Education – CPPTAE, linked to the Dean of People Management. Among the activities carried out by the commission, the process of distributing vacancies stands out, which has extreme strategic importance in the management of human resources at UFRN. This article aims to evaluate the quality of the information used in the process of distributing vacancies for UFRN's technical-administrative employees, considering the perspective of CPPTAE members. As for methodology, this work can be defined as applied social research with a quantitative approach, and characterized as descriptive. The data collection technique used was the questionnaire, pre-pared based on the PSP/IQ Model, by Lee at al (2002), and applied to all CPPTAE members. To ana-lyze the data, descriptive statistics were used. The research demonstrated the presence of deficient information quality attributes in the three documents evaluated. It is expected that the results pre-sented here will contribute to generating at UFRN the initiative to face the challenges posed, as well as serving as a reference for research in other institutions that require analysis and improvement in a similar context.